Piezoelectric sensor for acoustic wave detection in anisotropic systems - Barbosa, G. A. (2009)
This paper describes a seismic wave sensor, its readout electronics and data acquisition system. The seismic sensor is based on piezoelectric materials, which show the ability of transforming mechanical into electrical signals. In particular, the present sensor is based on a piezoelectric polymer, poly(vinilidene fluoride) as its main characteristics made it suitable for detecting the amplitude and frequencies involved in seismic events. After a general background on seismic events, waves and piezoelectric materials, the main steps on the sensor design and fabrication, the data acquisition system and the first test results are presented.